A nuclear phylogenomic study of the angiosperm order Myrtales, exploring the potential and limitations of the universal Angiosperms353 probe set. Issue 7 (23rd July 2021) - Maurin, Olivier; Anest, Artemis; Bellot, Sidonie; Biffin, Edward; Brewer, Grace; Charles‐Dominique, Tristan; Cowan, Robyn S.; Dodsworth, Steven; Epitawalage, Niroshini; Gallego, Berta; Giaretta, Augusto; Goldenberg, Renato; et al.
Abstract : Premise: To further advance the understanding of the species‐rich, economically and ecologically important angiosperm order Myrtales in the rosid clade, comprising nine families, approximately 400 genera and almost 14, 000 species occurring on all continents (except Antarctica), we tested the Angiosperms353 probe kit. Methods: We combined high‐throughput sequencing and target enrichment with the Angiosperms353 probe kit to evaluate a sample of 485 species across 305 genera (76% of all genera in the order). Results: Results provide the most comprehensive phylogenetic hypothesis for the order to date. Relationships at all ranks, such as the relationship of the early‐diverging families, often reflect previous studies, but gene conflict is evident, and relationships previously found to be uncertain often remain so. Technical considerations for processing HTS data are also discussed. Conclusions: High‐throughput sequencing and the Angiosperms353 probe kit are powerful tools for phylogenomic analysis, but better understanding of the genetic data available is required to identify genes and gene trees that account for likely incomplete lineage sorting and/or hybridization events.